TRAUMA HEALING BERBASIS SPIRITUALITAS ISLAMI: MODEL KONSELING PASCA-BENCANA - Elvina, Siska Novra; Wahyuni, Yeni Fitri; Hutagaol, Hummaira; Fadilah, Syifa Nur; Fitri, Wanda (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2025)
Natural disasters in Indonesia often cause diverse consequences. This situation requires a support model that focuses not only on clinical psychological aspects but also on the spiritual needs of the predominantly Muslim community. The research method used was a qualitative approach with a case study design in disaster-affected areas in West Sumatra. Data were obtained through in-depth interviews, observation, and documentation. Data analysis was conducted using thematic analysis techniques to identify relevant and implementable intervention patterns. The findings of the study indicate that trauma recovery based on Islamic spirituality can be implemented through six stages of intervention: trauma assessment, initial stability creation, individual or group counseling, spiritual strengthening, social and community support, and evaluation and follow-up. Each stage is based on values ​​found in the Qur'an and Hadith that encourage patience, trust, gratitude, and social brotherhood. This model has proven effective in helping victims reduce trauma symptoms, increase inner peace, and strengthen resilience in facing life after a disaster. Therefore, an Islamic-based trauma recovery approach can be a contextual and efficient model for Muslim communities in Indonesia. Keyword : Trauma Healing, Islamic Counseling, Spirituality, Post-Disaster, Resilience